Unholy war : terror in the name of Islam - Esposito, John L. (New York : Oxford University Press, 2002)
"The devastating September 11 attacks on the World Trade Center and the Pentagon left us stunned, angry, and uncomprehending. As it became clear that these horrifying acts had been committed in the name of Islam, we struggled to understand how religion could be used to justify the slaughter of innocents. The media, the government, and ordinary citizens alike sought answers to questions about Islam and its adherents. Who are the Muslim extremists who perpetrate such deeds? Why do they hate us? What do they hope to achieve? Does Islam really teach that such terrorists are holy warriors who will be rewarded with everlasting bliss?".
"In this book, John L. Esposito, one of the world's most respected scholars of political Islam, provides answers to these and many other questions that have arisen in the wake of the attacks. He clearly and carefully explains the teachings of Islam - the Quran, the example of the Prophet, Islamic law - about jihad or holy war, the use of violence, and terrorism. He chronicles the rise of extremist groups and examines their frightening worldview and tactics. Anti-Americanism (and anti-Europeanism), he shows, is a broad-based phenomenon that cuts across Arab and Muslim societies. It is not just driven by religious zealotry, but by frustration and anger at U.S. policy. Many Muslims are repelled by aspects of Western culture, and alarmed at its impact around the world. It is vital to understand, however, that the vast majority of Muslims are appalled by the acts of violence committed in the name of their faith."--BOOK JACKET.
Includes bibliographical references (p. [161]-168) and index.
English
Keywords: Terrorism -- Religious aspects -- Islam; Jihad; Islam and world politics; Anti-Americanism.